The completely revised handbook of coaching a developmental approach - McLean, Pamela D.; Hudson, Frederic M., 1934-; Hudson, Frederic M., 1934-; Honey, Greg.; ProQuest (Firm) (San Francisco : Jossey-Bass, 2012)
"When the first edition of The Handbook of Coaching was published in 1999 it was an innovative resource that offered a compendium of basic information about the then burgeoning field of adult coaching. Written for experienced and aspiring coaches, as well as for executives and human resource professionals interested in this expansive profession, this thoroughly revised and updated edition describes the essential underpinnings of successful coaching and includes a comprehensive, annotated list of books, articles, and other resources. The second edition also contains chapters that focus on how coaches can facilitate transformative change and explores how transitions create opportunity for development. This new edition also incorporates new advances in and research on coaching and adult development--pulling together data that is available online and new information that cannot be found anywhere else"--
pt. 1. An introduction to coaching -- pt. 2. Self as coach -- pt. 3. Theories informing the essentials of coaching -- pt. 4. A comprehensive methodology for the coaching engagement -- pt. 5. The client's life : coaching through transitions, human systems, and values -- pt. 6. Coaching in organizations -- pt. 7. Journey to coach mastery.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Employees -- Counseling of -- Handbooks, manuals, etc; Employees -- Coaching of -- Handbooks, manuals, etc; Personnel management -- Handbooks, manuals, etc; Mentoring in business -- Handbooks, manuals, etc; Electronic books